1985
DOI: 10.1002/chin.198538152
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: PALLADIUM‐CATALYZED DOUBLE CARBONYLATION OF ARYL HALIDES TO GIVE α‐KETO AMIDES. MECHANISTIC STUDIES

Abstract: Verschiedene Arylhalogenide wie (I) werden katalytisch bei der Behandlung mit sek. Aminen wie (II) in Gegenwart von CO (III) unter Bildung von α‐Ketoamiden (IV) [+ Nebenprodukte (V)] doppelt carbonyliert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Inoue and co-workers 247 found that the same reaction could be efficiently carried out using the chloro-bridged homobime-tallic (palladium) complex Pd 2 Me 2 (μ-Cl)(μ-dpfam) (Figure 21). Although the trends were similar to those obtained under mononuclear catalysis, 240 both reaction efficiency (total yield) and selectivity (di/monocarbonylation products ratio) were improved. Thus, acyclic secondary amines were suitable for the reaction, while pyrrolidine and piperidine showed high reactivity with moderate selectivity (Table 1).…”
Section: Palladium-catalyzed Double-carbonylative Aminationsupporting
confidence: 71%
“…Inoue and co-workers 247 found that the same reaction could be efficiently carried out using the chloro-bridged homobime-tallic (palladium) complex Pd 2 Me 2 (μ-Cl)(μ-dpfam) (Figure 21). Although the trends were similar to those obtained under mononuclear catalysis, 240 both reaction efficiency (total yield) and selectivity (di/monocarbonylation products ratio) were improved. Thus, acyclic secondary amines were suitable for the reaction, while pyrrolidine and piperidine showed high reactivity with moderate selectivity (Table 1).…”
Section: Palladium-catalyzed Double-carbonylative Aminationsupporting
confidence: 71%